Attenuation of glycemic responses by oat β-glucan solutions and viscoelastic gels is dependent on molecular weight distribution - Kwong, Melissa G. Y; Wolever, Thomas M. S; Brummer, Yolanda; Tosh, Susan M (Food & function, 2013)
Oat β-glucan attenuates postprandial glycemic responses when solubilized to form viscous solutions. High molecular weight (MW) β-glucan is associated with high solution viscosity, which is in turn associated with lower glycemic responses. However, low MW β-glucan is also able to form viscoelastic gels. The effect of low (145 000 g mol −1 ) and high (580 000 g mol −1 ) MW β-glucan presented as liquid drinks and gels on glycemic responses was determined. Healthy subjects ( n = 15) consumed 50 g glucose drinks with no β-glucan; 4 g low MW; or 4 g high MW β-glucan; and gels containing 4 g low MW; 2 g low plus 2 g high MW; or 3 g high plus 1 g low MW β-glucan. Overall, β-glucan solutions elicited lower glycemic responses than gels. For gels, peak blood glucose rise (PBGR) decreased with increasing dose of high MW β-glucan ( r 2 = 0.976, P > 0.05), and PBGR for the gel with 3 g high-MW was lower than for the control ( P < 0.05). However, β-glucan gels retained glucose better than solutions under in vitro analysis. Observed effects were found to be related to the rheological properties of the foods. β-Glucan solutions and not gels effectively attenuated in vivo glycemic responses. Oat β-glucan viscous solutions, but not gels, attenuate postprandial glycemic responses.